2023
DOI: 10.1039/d3ce00729d
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structural and photoluminescence properties of Eu3+ doped MgZn2(PO4)2 phosphors by R+ (R = Li, Na, K) charge compensation

Yongping Huang,
Zheng Liu,
Yuexu Xiong
et al.

Abstract: The effect of the charge compensation agent R+ (R = Li, Na, K) on the luminescence properties of MgZn2(PO4)2:Eu3+ phosphors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Based on elements (Mn and Zn), a lot of research is being done to get the materials with the desired functional properties. [40][41][42][43][44][45][46][47][48][49] Studies on Mn-doped Zn 3 P 2 nanoparticles have not been reported so far. These factors and the interesting properties exhibited by the Mn-doped Zn 3 P 2 system are the motivation to carry out this study.…”
mentioning
confidence: 99%
“…Based on elements (Mn and Zn), a lot of research is being done to get the materials with the desired functional properties. [40][41][42][43][44][45][46][47][48][49] Studies on Mn-doped Zn 3 P 2 nanoparticles have not been reported so far. These factors and the interesting properties exhibited by the Mn-doped Zn 3 P 2 system are the motivation to carry out this study.…”
mentioning
confidence: 99%